2018
DOI: 10.1002/cpim.40
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometry: An Overview

Abstract: Flow cytometry is a technology that provides rapid multi-parametric analysis of single cells in solution. Flow cytometers utilize lasers as light sources to produce both scattered and fluorescent light signals that are read by detectors such as photodiodes or photomultiplier tubes. These light signals are converted into electronic signals that are analyzed by a computer and written to a standardized format (.fcs) data file. Cell populations can be analyzed and/or purified based on their fluorescent or light sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
353
0
24

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 535 publications
(378 citation statements)
references
References 7 publications
1
353
0
24
Order By: Relevance
“…As Mtb is a strict human pathogen, there is also an advantage to study Mtb in humanized model systems. Flow cytometry is a powerful technology that offers the possibility to assess multiple phenotypic and functional characteristics of single cells in suspension 22 , something that could be fairly challenging with adherent cells such as macrophages that are also known to be autofluorescent 23 , 24 . In addition to chemical detachment…”
Section: Introductionmentioning
confidence: 99%
“…As Mtb is a strict human pathogen, there is also an advantage to study Mtb in humanized model systems. Flow cytometry is a powerful technology that offers the possibility to assess multiple phenotypic and functional characteristics of single cells in suspension 22 , something that could be fairly challenging with adherent cells such as macrophages that are also known to be autofluorescent 23 , 24 . In addition to chemical detachment…”
Section: Introductionmentioning
confidence: 99%
“…For instance in the developing neocortex it was shown that dynamic waves of transcriptional programs drive neuronal differentiation and temporal patterning (Telley et al, 2019;Telley et al, 2016). Given that scRNA-Seq detects mRNA, flow cytometry represents a useful complementary approach that allows multiparametric analyses of large numbers of cells at single cell resolution, allowing the detection of proteins or DNA content (McKinnon, 2018). In addition, flow cytometry provides quantitative data at population level that is complementary to clonal analyses performed in the developing neocortex that provide quantitative information on clone size and composition (Beattie et al, 2020;Gao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…They are generally used to quantify DNA and to observe cells distribution during the cell cycle (Propidium Iodide, 7-Aminoactinomycin D or 7-AAD, DyeCycle Violet, 4 ,6-Diamidino-2-phenylindole or DAPI, Hoescht 33342), to estimate cell viability (PI, DAPI), to isolate chromosomes for sorting (Hoescht 33342, Chromomycin A3), to quantify apoptotic cell fractional DNA content (Acridine Orange or AO, 7-AAD), etc. [109,110] These dyes are frequently used for cell migration and tracking analysis due to their high retention. Nevertheless, DNA-binding dyes are not applicable for proliferation analysis because the content (and intensity) of the dye decreases after each cell cycle [111].…”
Section: Cell Tracking Dyesmentioning
confidence: 99%